REPRESENTATION OF NATURE AND MAN IN PRACTICAL PHILOSOPHY OF DESCARTES - А. M. Malivskyi; К. V. Soкоlоvа (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Modern philosophy is presented as practical and is based on the necessity to give a new meaning and interpretation to moral and ethical problems. Purpose of the paper is to comprehend specifics of modern perception of Cartesian interpretation of nature and man that implies consistent stages of technomorphic perception, critical analysis of its authenticity in research literature and understanding of rehabilitation tendency of Descartes' ethics as practical philosophy. Originality. The research is focused on the problem of technomorphism authenticity in the process of understanding and interpreting Descartes' practical philosophy. The authors are trying to defend rationale for phenomena interpretation concerning Descartes' technocratic orientation in terms of his ethical search. Critical interpretations of limited technomorphic perception of nature and man should be understood as some transition period towards ethics rehabilitation as practical philosophy. The study of Descartes on nature in its broad sense as metaphysical basis of his ethics has been revealed and analyzed. Conclusions. Technocratic interpretation of Descartes study is a superficial and distorted form of his practical philosophy interpretation. Until recently technomorphic perception of Descartes' study dominated in scientific literature, which has significantly determined limited perception of nature and man combined with superficial ethics perception. Critical rethinking of the developed Descartes' interpretations in recent scientific papers solves at the same time the tasks of theoretical denial of simplistic world perception and gives grounds for ethics rehabilitation as authentic form of its practical philosophy expression. One form of rehabilitation expression is increased attention to the concept of nature in its broad sense, which is a basis for its humanistic and ethical vision of philosophical tasks.